(untitled) (Bangladesh Journal of Pharmacology, 2017)
Hamelia patens is used in folk medicine in the treatment of nervous shock. The present study deals to evaluate the antidepressant-like effects of chloroform and methanol extracts of H. patens on the performance of male mice and GC-MS profiling of bioactive extract. Mice were given extracts orally in acute doses of 100 and 200 mg/kg daily for 7 days and then subjected to forced swim test, tail suspension test and open field test. Imipramine (10 mg/kg/day, p.o.) and fluxetamine (10 mg/kg/day, p.o.) were used as the standard in forced swim test and tail suspension test respectively. GC-MS profiling of chloroform extract was performed to find out the chemical constituents in bioactive fraction. After one-week treatment, the chloroform extract (100 and 200 mg/kg/day, p.o.) significantly reduced immobility time in forced swim test and tail suspension test (p<0.05). All extracts did not show any significant change in the locomotor activity in open field test. These data indicate that the extract of H. patens possesses antidepressant-like properties in mice without any significant effect on locomotor activity. Video Clip of Methodology: 4 min 06 sec: Click to watch